2008
DOI: 10.1037/0021-9010.93.1.189
|View full text |Cite
|
Sign up to set email alerts
|

Motherhood: A potential source of bias in employment decisions.

Abstract: Results of 2 experimental studies in which job incumbents were said to be applying for promotions to traditionally male positions demonstrated bias against mothers in competence expectations and in screening recommendations. This bias occurred regardless of whether the research participants were students (Study 1) or working people (Study 2). Although anticipated job commitment, achievement striving, and dependability were rated as generally lower for parents than for nonparents, anticipated competence was uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
220
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(243 citation statements)
references
References 38 publications
15
220
1
7
Order By: Relevance
“…Overall our findings are consistent with recent research by Heilman and Okimoto, (2008) which also asked undergraduate students and working adults to evaluate hypothetical workers described in vignettes. They found that anticipated job commitment and anticipated achievement striving were negatively affected by parental status, in both men and women.…”
Section: Discussionsupporting
confidence: 82%
“…Overall our findings are consistent with recent research by Heilman and Okimoto, (2008) which also asked undergraduate students and working adults to evaluate hypothetical workers described in vignettes. They found that anticipated job commitment and anticipated achievement striving were negatively affected by parental status, in both men and women.…”
Section: Discussionsupporting
confidence: 82%
“…However, this does not imply that female dendrochronologists do not experience other types of gender bias and we do not intend to belittle the challenges that women dendrochronologists have overcome to gain the same level of recognition of their research as their male counterparts. If anything we laud the efforts of women researchers who overcome well-documented biases in hiring processes (Levin et al 2005;Schmader et al 2007), promotion decisions (Carr et al 2003;Heilman and Okimoto 2008), tenure decisions (Luzzadder-Beach and Macfarlane 2000), and grant awarding (Bornmann and Daniel 2005;Bornmann et al 2007) to achieve the same level of success as their male counterparts. …”
Section: Resultsmentioning
confidence: 99%
“…Of interest in our study and that of Heilman and Okimoto (2008) are the undergraduate attitudes, which are not coloured by current or specific organisational culture but preconceptions that are likely to be carried forward into the workplace. These are not only likely to perpetuate the long hours culture in the UK but to be of continuing detriment to women.…”
Section: Discussionmentioning
confidence: 99%